Aerobic and facultative bacteria: working horses at the service of anaerobic digestion - Duarte, Maria Salomé Lira (2019)
It is clear that aerobic and facultative anaerobic bacteria have an important role in the first steps of the anaerobic digestion (AD) process, especially when complex organic compounds are degraded. However, their diversity, abundance and function, related to the fine control of process variables such as pH and ORP, and the potential establishment of networks with methanogens and acetogens are far from being fully understood. Here we show some examples demonstrating that microaerophilic and aerobic conditions are critical for accelerating the methane production rates from hydrophobic compounds such as lipids and hydrocarbons. In the later case, a combination of aerobic with methanogenic conditions allow to convert hydrocarbons to methane at accelerated rates, with bacterial lipids as main intermediates. We believe that hybrid fine-controlled microaerophilic AD processes will emerge as the next generation of applications of AD technology to boost the methane production rate from a myriad of anaerobically slow degraded complex substrates